2011
DOI: 10.1590/s1415-65552011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Comprometimento, satisfação e cooperação no trabalho: evidências da primazia dos aspectos morais e das normas de reciprocidade sobre o comportamento

Abstract: O objetivo no presente estudo é verificar as relações entre comprometimento organizacional, satisfação e cooperação no trabalho. A satisfação é posicionada como construto antecedente das dimensões do comprometimento e a cooperação como consequente comportamental desses dois construtos. O método de pesquisa adotado foi o levantamento (survey), com uso de amostragem não probabilística por conveniência. Após exame da literatura e desenvolvimento das hipóteses, foram coletados 331 questionários válidos, que foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
4
0
6
Order By: Relevance
“…Although these studies use different instruments to measure organizational learning, both identified a relation between the constructs. On the other hand, the work of Maciel and Camargo (2011) and Palacios, Almeida and Rezende (2011) dealt with the relationship between commitment and satisfaction in work, finding positive results in both.…”
Section: Theoretical Referencementioning
confidence: 99%
“…Although these studies use different instruments to measure organizational learning, both identified a relation between the constructs. On the other hand, the work of Maciel and Camargo (2011) and Palacios, Almeida and Rezende (2011) dealt with the relationship between commitment and satisfaction in work, finding positive results in both.…”
Section: Theoretical Referencementioning
confidence: 99%
“…The integrity and the image of the institution are meaningful because the members are proud to serve in the church, relating to satisfaction with the organization, one of the reasons for their commitment (Maciel & Camargo, 2011). Members value transparency and integrity.…”
Section: Integrity and Image Of The Institutionmentioning
confidence: 99%
“…Maciel and Camargo (2011) state that the commitment to work is influenced by the overall satisfaction with the organization, both the emotional connection as well as what they would lose by leaving it. People also get involved for the pleasure of working for a cause, to feel useful, and their own psychological well-being.…”
mentioning
confidence: 99%
“…Os objetivos e os interesses organizacionais norteiam as atividades que procedem de distintas pressões normativas; nesse sentido, a dimensão moral, comumente internalizada nas organizações, orienta as atitudes dos trabalhadores. O comprometimento é considerado fruto de uma impetuosa obrigação (Maciel & Camargo, 2011).…”
Section: Comprometimento Organizacionalunclassified